Genetic Diversity of Mindi (Melia azedarach L.) in Community Forests West Java Assessed by Microsatellite Markers KERAGAMAN GENETIK MINDI (Melia azedarach L.) PADA HUTAN RAKYAT DI JAWA BARAT DENGAN PENANDA MIKROSATELLIT - Laswi Irmayanti; Iskandar Zulkarnain Siregar; Prijanto Pamoengkas (Jurnal Silvikultur Tropika, 2015)
Mindi (Melia azedarach L.) is mostly found in community forests of West Java. One of the factors that affect productivity of mindi plantation is high quality seed that is not easily available. Seed sources of mindi should be established based on the status of genetic variation, preferably the one with high genetic variation. However, information on the status of genetic variation is always lacking. The research objective was to estimate genetic variation within and between populations of mindi in West Java community forests based on microsatellites. Six mindi populations were selected in the following villages: Nagrak (Bogor),Babakan Rema (Kuningan), Padasari (Sumedang), Legok Huni (Wanayasa), Sukakarya (Bogor) and Gambung (Bandung).The results showed that average number of alleles was 2.750, PLP (percentage of polymorphic loci) was 91.67%, and the genetic diversity within populations (He) was 0.366. The highest genetic diversity was found in Padasari (He = 0.454), and the lowest one was in Babakan Rema (He = 0.269). The genetic difference between populations (Fst) was 0.3030. Cluster analysis showed three groupings in which the first and second clusterconsisted of Nagrak and Padasari, as well as Babakan Rema, Gambung and Sukakarya, respectively. On the other hand Legok Huni was separated alone. The findings provided information on the moderate status of genetic diversity that may be considered during the selection and establishment of seed sources.Key words : community forests, genetic diversity microsatellite, mindi (Melia azedarach L.)